Penerapan Green Accounting Berbasis Tri Hita Karana Pada Perusahaan Sanken - Parwati, Khofifah Indah; Leniwati, Driana; Wahyuni, Endang Dwi; Juanda, Ahmad (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2025)
This study aimed to determine whether the company applied green accounting principles based on Tri Hita Karana values at Sanken Company, East Denpasar, Bali. Using an interpretive paradigm, this study analyzed the application through a case study approach. Data were obtained through in-depth interviews with the accounting department as key informants. A snowball sampling method was used to add more informants. The interview results were grouped, and data reduction was carried out before analysis and drawing conclusions or verifications. Triangulation was also conducted using different questioning techniques to ensure the validity of the data, involving employees and the surrounding community as additional informants. By applying the triangulation technique, the researcher was confident in the validity of the collected data. The findings revealed that green accounting was interpreted as Parahyangan (God), Pawongan (Humans), and Palemahan (Environment). Empirically, in a broader sense, green accounting was not only understood as an environmental financial concept but also as a way to build relationships with the community and maintain faith in God through environmental preservation.